Stapedius tendon ossification: Meaning of the ossicle of Paaw - Álvarez-Buylla Carmino, M. (2018)
Introduction: Stapes tendon ossification is an uncommon ossicular congenital malformation with autosomal dominant inheritance. Globular supernumerary sesamoid bone within the stapes tendon was described by several anatomists. We have found a fixed stapes by a bony bridge between pyramidal eminence and stapes head keeping the habitually morphology and consistency of the stapedial tendon. Material and method: 40 year old female patient presented with progressive bilateral hearing loss history with similar family history. We present clinical examination, complementary studies, treatment and course. Discussion: Patients with a conductive or mixed hearing loss, normal or low compliance, and acoustic reflex with inverted pattern in 2000 Hz, CT images can be diagnostic in 25-67 % of the cases, facilitating treatment planning. A linear image attenuation of soft tissues in CT from the pyramidal eminence to the stapes is suggestive of a congenital ossification of the stapedial tendon. A small globular or rounded image inside the stapes tendon corresponds to the existence of Paaw bone. Elimination of the bony bridge preserving the integrity of the ossicular chain and its tendons restores the problem of hearing loss.